The importance of organic agriculture in tourism rural - Privitera, Donatella (Applied Studies in Agribusiness and Commerce, 2010)
Many farmers, in addition to normal farming activity, have already turned to agritourism as a source of additional farm income and opportunities. There are numerous benefits from the development of agritourism: it may strengthen local economy, create job opportunities and new businesses; develop and promote training and certification programs to introduce young people to agriculture and environment. Agritourism helps preserve rural lifestyles and landscape and also offers the opportunity to provide "sustainable" or "green" tourism. Organic agriculture is a cultural evolution that finds its origins in a environmentalist culture. Furthermore the focus on these products is due to demand on healthy foods with high quality standard limiting chemical substances usage. It’s clear the link of the organic agriculture with agritourism and tourism services. They have a considerable role in the future development of rural areas. The purpose of this paper was to identify and examine those factors that have helped rural communities successfully develop agritourism, in particular organic agritourism and its entrepreneurship opportunities. Several focus groups were conducted with local business persons and leaders about a applicative case of South Italy area.